Meningkatkan Keaktifan dan Hasil Belajar IPS Melalui Metode Time Token Siswa Kelas VIII D SMP Negeri 24 Kota Jambi - Tianna Simanjuntak (Universitas Batanghari Jambi, 2019)
This research was motivated because of the students of class VIII D of SMP 24 Jambi tend to be passive and challenging to be invited to be more active, creative, and confident. For example, students have not dared to ask if they do not understand. In addition to that, the studentswere silent and did not express their opinionsin a class discussion. Thus, the learning processof the classroom was less effective and conducive. One of the steps taken is to use the Time Token learning method. In this method, students are required to be more active in expressing their opinions and to be able to listen to the opinions of others. The purpose of this study is to find out how big the effect of the Time Token method can improve student activity and learning outcomes in social studies. This research is a class action research (PTK) with the class VIII D as the subject in the oddsemester. Data collection methodologies used in this study are experiment and observation methods. The collected data was analyzed by qualitative descriptive analysis. The results showed that there was an increase in activity and learning outcomes in social studies subjects after using the Time Token learning method during the implementation of the action.The average activity of the first cycle was 69.82% and it increased to 88.42%in the second cycle. Furthermore, the increase in student learning outcomes that have fulfilled the completeness value was of 7.89%in the first cycle butin the second cycle there was an increase, which became to 92.11.